Preciptation of vanadates from their water solutions using different protonated amine compounds (Latakia University Journal -Basic Sciences Series, 2018)
Many chemical compounds (bases, inorganic acids, salts) have been used to find a suitable solvent for vanadium oxide And determine optimal conditions for its Dissolution.The best of them was sodium hydroxide at 2M concentration. The solubility was 100% at 90 °C and the solubilitys time was 30 min. The number of motor cycles was 800 cycles / min and the liquid / solid ratio was 200 g / L.In addition,the best amino protonadted compounds were used to precipitate vanadates from their solutions (monoethanolamine, diphenylamine, hydrazine, hydroxide amine hydrochloride, urea) with several inorganic acids (HCl, H2SO4, HNO3) and 1: 1 acid/base was monoethanolamine protonated with concentrated sulfur acid .